Hukum Politik dalam Praktik: Bagaimana Kekuasaan Politik Mempengaruhi Hasil Hukum di Asia Tenggara - Maulana Anwar; Afif Noor (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study examines the phenomenon of political jurisprudence in Southeast Asia, emphasizing the persistent intersection between judicial institutions and political power. Using qualitative content analysis of regional reports, particularly the UNDP’s Judicial Integrity and Independence in Southeast Asia (2023–2024), the research identifies patterns of external pressure, limited transparency, and constrained judicial ethics across six ASEAN countries. Findings reveal that political influence remains prevalent in judicial appointments, decision-making, and resource allocation, reflecting structural dependence on the executive branch. Informal mechanisms such as patronage networks, selective sanctions, and budgetary control further weaken judicial autonomy and discourage resistance to political authority. These dynamics foster a culture of strategic conformity, where judicial decisions often align with dominant political interests rather than constitutional or human rights principles. Consequently, public trust in judicial integrity erodes, undermining both democratic accountability and access to justice. The study concludes that enhancing judicial independence in Southeast Asia requires not only institutional reform but also cultural transformation within the judiciary promoting ethical resilience, transparency, and professional integrity to resist political co-optation and strengthen the rule of law.